2014
DOI: 10.2471/blt.13.135145
|View full text |Cite
|
Sign up to set email alerts
|

Measles incidence and reporting trends in Germany, 2007–2011

Abstract: ObjectiveWe aimed to quantify progress towards measles elimination in Germany from 2007 to 2011 and to estimate any potential underreporting over this period.MethodsWe determined the annual incidence of notified cases of measles – for each year – in northern, western, eastern and southern Germany and across the whole country. We then used measles-related health insurance claims to estimate the corresponding incidence.FindingsIn each year between 2007 and 2011, there were 6.9–19.6 (mean: 10.8) notified cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
0
22
0
9
Order By: Relevance
“…One known limitation in measles case surveillance is that it is subject to underreporting. Studies have demonstrated underreporting in outbreak settings; one study in Germany demonstrated an average of three times lower rates of reporting to the mandatory notification system compared to health insurance claim submissions by doctors [ 45 , 46 ]. The Measles Strategic Planning (MSP) tool developed by the WHO for the analysis of immunization and surveillance data at a national level, also demonstrates underreporting in non-outbreak settings in countries across the globe [ 47 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…One known limitation in measles case surveillance is that it is subject to underreporting. Studies have demonstrated underreporting in outbreak settings; one study in Germany demonstrated an average of three times lower rates of reporting to the mandatory notification system compared to health insurance claim submissions by doctors [ 45 , 46 ]. The Measles Strategic Planning (MSP) tool developed by the WHO for the analysis of immunization and surveillance data at a national level, also demonstrates underreporting in non-outbreak settings in countries across the globe [ 47 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Outbreak-related incidence estimates ranged between 12 and 32 per 100,000 inhabitants. One study examining the epidemiology of measles from 2007 to 2011 (Takla et al 2014) showed large geographical differences in incidence of measles with the highest incidence in southern Germany. Another study presenting results for 1999 to 2001 (Tischer et al 2002) found that most cases of measles occurred in southern Germany and in North Rhine-Westphalia.…”
Section: Resultsmentioning
confidence: 99%
“…Another study presenting results for 1999 to 2001 (Tischer et al 2002) found that most cases of measles occurred in southern Germany and in North Rhine-Westphalia. Two studies (Mette et al 2011; Takla et al 2014) compared results of the analyses of surveillance data and ASHIP claims data and found that incidence estimates based on ASHIP data were higher than estimates based on notification data. Some studies only reported absolute numbers of cases instead of presenting data as incidence rates (see Table 2 for details).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Case E2 was most likely infected by an unknown intermediate case, who in turn was most likely infected by Case E1. The problem of under-reporting of measles has been acknowledged elsewhere [ 28 - 30 ].…”
Section: Discussionmentioning
confidence: 99%